2000
DOI: 10.1110/ps.9.11.2142
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a mutant peptide derived from ubiquitin: Implications for protein folding

Abstract: The formation of the N-terminal b-hairpin of ubiquitin is thought to be an early event in the folding of this small protein.Previously, we have shown that a peptide corresponding to residues 1-17 of ubiquitin folds autonomously and is likely to have a native-like hairpin register. To investigate the causes of the stability of this fold, we have made mutations in the amino acids at the apex of the turn. We find that in a peptide where Thr9 is replaced by Asp, U~1-17!T9D, the native conformation is stabilized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 28 publications
5
59
0
Order By: Relevance
“…The estimated population of the folded hairpin was only 64%; nevertheless, the NMR resonances were unusually well resolved, and it was possible to attribute particular NOEs to the unfolded state. This deconvolution of the NOE data allowed the calculation of folded-state structures with good geometry and no distance restraint violations Ͼ 0.5 Å (27). The precision of the ensemble (backbone rmsd ϭ 0.59 Å) is close to that of the trpzips (see Table 3); however, as those authors note, the structure of the folded state of U(1-17)T9D may be more dynamic than indicated by the final ensemble (27).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The estimated population of the folded hairpin was only 64%; nevertheless, the NMR resonances were unusually well resolved, and it was possible to attribute particular NOEs to the unfolded state. This deconvolution of the NOE data allowed the calculation of folded-state structures with good geometry and no distance restraint violations Ͼ 0.5 Å (27). The precision of the ensemble (backbone rmsd ϭ 0.59 Å) is close to that of the trpzips (see Table 3); however, as those authors note, the structure of the folded state of U(1-17)T9D may be more dynamic than indicated by the final ensemble (27).…”
Section: Resultsmentioning
confidence: 83%
“…3A). Cross-strand tryptophan † Very recently, the structure of U(1-17)T9D, a variant of the N-terminal ␤-hairpin of ubiquitin, was reported (Protein Data Bank code 1E0Q) (27). The estimated population of the folded hairpin was only 64%; nevertheless, the NMR resonances were unusually well resolved, and it was possible to attribute particular NOEs to the unfolded state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ala, Asp, and Gly occupy the (i ϩ 1) to (i ϩ 3) positions, respectively. Asp exhibits the highest statistical occurrence at the (i ϩ 2) position (30)(31)(32), whereas Gly is suited best to adopt the positive ͞-dihedral angles at the bulge position (i ϩ 3) in the type-I G1 bulge turn geometry (28,(32)(33)(34). The sequences corresponding to variants 3 and 4 were designed to test whether repositioning the functional Arg residue at the (i ϩ 1) or (i ϩ 2) position in a shorter sequence expected to adopt a type-I G1 bulge loop would yield WW domains with ligand-binding affinities comparable with variant 1.…”
mentioning
confidence: 99%
“…Several peptide models with a basic hairpin structure have been used to examine the relationship between turn sequence and turn conformation. They are either designed peptides (8)(9)(10)(11)(12)(13) or short peptide segments adopted from protein sequences like ubiquitin (14)(15)(16)(17) and the protein G B1 domain (18,19). From these studies, there is little doubt that turn residues determine the conformation and stability of ␤-hairpins.…”
mentioning
confidence: 99%